(3GdeNJGQ ef eOjM GdeNJGQs - (3eLghds; (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s
(3ChdgG (B:s
(3gPG eG GNJjQ ef eOjM GdfHj Udi Gddg Ydjg hSde ef fXe GdUQUQj CMSf Gddg Jhajbg hSgd Edi GdNjQGJ WQjbg s
(3BNQgG (B:s
(3ef bUjOI eWhdINJGegG(B: (3MeOkG cKjQkG WjHkG eHGQckG ajg EPG cQqQg GdeQA LdG Je GdeNJGQ ef OjhGf GdUQUQj QMeg Gddg, HMeO Gddg hYhfg s
(3fSNI KGfjI eQJHI Ydi GdbhGajs
(3hHChdgG JedcGJ heWGdYGJ efgG (B990(3g```s
(3YdjgG ebGHdI bGe HgG eMeO Hf SYjO Hf YHOGddg Hf SYjO GdMdHjs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs